Neuroprotective Effects of Myrtle Berry By-Product Extracts on 6-OHDA-Induced Cytotoxicity in PC12 Cells - Debora Dessì; Giacomo Fais; Paolo Follesa; Giorgia Sarais (Antioxidants)
The rising global focus on healthy lifestyles and environmental sustainability has prompted interest in repurposing plant-based by-products for health benefits. With increasing life expectancy, the incidence of neurodegenerative diseases—characterized by complex, multifactorial mechanisms such as abnormal protein aggregation, mitochondrial dysfunction, oxidative stress, and inflammation—continues to grow. Medicinal plants, with their diverse bioactive compounds, offer promising therapeutic avenues for such conditions. Myrtus communis L., a Mediterranean plant primarily used in liquor production, generates significant waste rich in antioxidant and anti-inflammatory properties. This study explores the neuroprotective potential of Myrtus berry by-products in a cellular model of neurodegeneration. Using PC12 cells exposed to 6-hydroxydopamine (6-OHDA), we assessed cell viability via MTT assay and measured reactive oxygen species (ROS) production using DCFDA fluorescence. Additionally, we analyzed the expression of genes linked to oxidative stress and neuronal function, including AChE, PON2, Grin1, Gabrd, and c-fos, by RT-PCR. Our findings reveal that Myrtus extract significantly protects against 6-OHDA-induced cytotoxicity, reduces ROS levels, and modulates the expression of key stress-related genes, underscoring its potential as a neuroprotective agent. These results highlight the therapeutic promise of Myrtus extracts in mitigating neurodegenerative processes, paving the way for future interventions.